Species-dependent impact of immunosuppressive squalene-gusperimus nanoparticles and adipose-derived stem cells on isolated human and rat pancreatic islets. Issue 1 (31st December 2022) - Navarro Chica, Carlos E.; Qin, Tian; Pinheiro-Machado, Erika; de Haan, Bart J.; Faas, M.M.; Smink, Alexandra M.; Sierra, Ligia; López, Betty L.; de Vos, Paul
ABSTRACT: Transplantation of pancreatic islets is a promising approach to controlling glucose levels in type 1 diabetes mellitus (T1DM), but islet survival is still limited. To overcome this, islet co-culture with mesenchymal stromal cells (MSCs) together with safe immunosuppressive agents like squalene-gusperimus nanoparticles (Sq-GusNPs) may be applied. This could support islet survival and engraftment. Here, we studied how Sq-GusNPs and adipose-derived stem cells (ASCs) influence islets response under pro-inflammatory conditions. Through qRT-PCR, we studied the expression of specific genes at 24 hours in human and rat islets and ASCs in co-culture under indirect contact with or without treatment with Sq-GusNPs. We characterized how the response of islets and ASCs starts at molecular level before impaired viability or function is observed and how this response differs between species. Human islets and ASCs responses showed to be principally influenced by NF-κB activation, whereas rat islet and ASCs responses showed to be principally mediated by nitrosative stress. Rat islets showed tolerance to inflammatory conditions due to IL-1Ra secretion which was also observed in rat ASCs. Human islets induced the expression of cytokines and chemokines with pro-angiogenic, tissue repair, and anti-apoptotic properties in human ASCs under basal conditions. This expression was not inhibited by Sq-GusNPs. Our results showed a clear difference in the response elicited by human and rat islets and ASCs in front of an inflammatory stimulus and Sq-GusNPs. Our data support the use of ASCs and Sq-GusNP to facilitate engraftment of islets for T1DM treatment. Graphical abstract: uf0001